2001
DOI: 10.1186/gb-2001-2-4-research0010
|View full text |Cite
|
Sign up to set email alerts
|

A simple model based on mutation and selection explains trends in codon and amino-acid usage and GC composition within and across genomes

Abstract: Background:Correlations between genome composition (in terms of GC content) and usage of particular codons and amino acids have been widely reported, but poorly explained. We show here that a simple model of processes acting at the nucleotide level explains codon usage across a large sample of species (311 bacteria, 28 archaea and 257 eukaryotes). The model quantitatively predicts responses (slope and intercept of the regression line on genome GC content) of individual codons and amino acids to genome composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
138
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(144 citation statements)
references
References 69 publications
6
138
0
Order By: Relevance
“…Because context-dependent nucleotide biases also influence codon bias (30,31), one would therefore expect growth temperature to correlate with a mutational effect on codon bias. Furthermore, recent work has shown that patterns of codon bias across many different organisms, both thermophilic and mesophilic, can be explained by a single mutational model dependent on positionspecific nucleotide parameters (23). Finally, elevated temperatures result in markedly elevated rates of DNA damage (44), but GC content does not correlate with optimal growth temperature (30), suggesting a role for biases that are not captured by simple GC content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because context-dependent nucleotide biases also influence codon bias (30,31), one would therefore expect growth temperature to correlate with a mutational effect on codon bias. Furthermore, recent work has shown that patterns of codon bias across many different organisms, both thermophilic and mesophilic, can be explained by a single mutational model dependent on positionspecific nucleotide parameters (23). Finally, elevated temperatures result in markedly elevated rates of DNA damage (44), but GC content does not correlate with optimal growth temperature (30), suggesting a role for biases that are not captured by simple GC content.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these cases, evidence exists that selection at different steps during protein expression shapes codon bias. In addition, global forces differentiate the codon bias of genes between different organisms: species-specific codon bias is strongly correlated with overall genome percentage GC content (22,23), genes from organisms with similar phylogeny or with similar tRNA content have similar codon bias (22), and an organism's optimal growth temperature influences the codon bias of its genes (24). Most of these global forces are thought to be mutational, acting on all DNA sequences, although it has also been argued that growth temperature exerts a selective force on mRNA structure (25) and codon bias (24).…”
mentioning
confidence: 99%
“…She woke at 2 a.m. to find him trembling with excitement after solving a thorny computational problem. The program he had devised crunched through protein-coding sequences from 600 species spanning all domains of life to show that very simple rules involving mutation and selection could explain a major puzzle about DNA: why different organisms prefer different coding sequences for the same amino acid 4 .…”
Section: Everything Of Interestmentioning
confidence: 99%
“…Unequal frequencies of the four bases may be due to mutation bias, maintained by natural selection, or result from a balance between these two forces (1,2). If mostly maintained by selection, base-composition bias will change when the efficiency of selection is compromised, with the direction and magnitude of change depending on the relative power and direction of pressure from both mutation and selection.…”
mentioning
confidence: 99%